2013
DOI: 10.11606/issn.2318-3659.v50i1p33-42
|View full text |Cite
|
Sign up to set email alerts
|

Evidências neuroquímicas e comportamentais do efeito ansiogênico da deltametrina em ratos

Abstract: Pyrethroid insecticides are extensively used for pest control around the house, flea prevention for pets, and plant sprays for the home and in agriculture. Deltamethrin (DTM) is a Type II pyrethroid insecticide used to control a variety of insects in agriculture and domestic environments. The present study investigated the possible anxiogenic effects of DTM (1, 3, and 10 mg/kg) in rats using behavioral and neurochemical methods. We assessed general locomotor activity and behavior in the elevated plus maze and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Bhattacharya et al reported that decreased activity after DTM exposure might result from enhanced anxiety because they observed a decreased number of crossings, a decline in time spent in the inner zone, and increased defecation scores in the DTM group (30). Ricci et al reported that behavioral and neurochemical methods induced the anxiogenic effects of DTM in rats, and DTM had a similar effect to anxiogenic drugs via serotonin neurotransmission (31). Similarly, in our study, DTM decreased locomotion, prolonged immobility, rearing repetition, and decreased the time spent in the inner zone.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Bhattacharya et al reported that decreased activity after DTM exposure might result from enhanced anxiety because they observed a decreased number of crossings, a decline in time spent in the inner zone, and increased defecation scores in the DTM group (30). Ricci et al reported that behavioral and neurochemical methods induced the anxiogenic effects of DTM in rats, and DTM had a similar effect to anxiogenic drugs via serotonin neurotransmission (31). Similarly, in our study, DTM decreased locomotion, prolonged immobility, rearing repetition, and decreased the time spent in the inner zone.…”
Section: Discussionsupporting
confidence: 86%
“…The development of anxiety can be strongly influenced by toxicological factors or various activated neurotransmitter mechanisms of DTM. Experimental studies have shown that increased neurotransmitter release at multiple levels in cortical regions improves the efficacy of interconnected networks in anxiety (30,31). A further possible finding is that DTM is responsible for anxiety-related behavioral changes in the marble burying test and OFT; therefore, it can be used to design various experimental models in translational neuroscience.…”
Section: Discussionmentioning
confidence: 99%